The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/pas.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Tumor With Melanocytic Differentiation and ACTIN-MITF Translocation

Abstract: Clear cell morphology is an uncommon finding in tumors. A subset of clear cell neoplasms also shows melanocytic differentiation, including clear cell sarcoma, PEComa, and some subtypes of renal cell carcinoma. A hallmark of these tumor types is the activation of a member of the MIT/TFE family of transcription factors, which includes MITF, TFE3, TFEB, and TFEC. Microphthalmia transcription factor (MITF is the master regulator of melanin synthesis, while TFEB plays a critical role in lysosome biogenesis. Cytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Based on these data, PEM and atypical Spitz tumor might represent melanocytic tumors of low-grade (mostly lymphotropic) malignancy different from "classical" melanoma: it seems thus reasonable to include atypical Spitz tumor into the "melanocytoma" rubric, as suggested since the beginning (49). Interestingly enough, the list of putative low-grade melanocytic malignancies with a peculiar genetic and morphologic profile has been growing for the last years and has thus been increasingly supporting the concept itself (50)(51)(52)(53). An example of CRTC1-TRIM11 (50) fused melanocytoma is provided in Figure 2; like several other melanocytomas, such a putatively low-grade malignant melanocytic tumor does not likely progress from a common nevus.…”
Section: Nevi As Potential Precursors To Melanomamentioning
confidence: 90%
“…Based on these data, PEM and atypical Spitz tumor might represent melanocytic tumors of low-grade (mostly lymphotropic) malignancy different from "classical" melanoma: it seems thus reasonable to include atypical Spitz tumor into the "melanocytoma" rubric, as suggested since the beginning (49). Interestingly enough, the list of putative low-grade melanocytic malignancies with a peculiar genetic and morphologic profile has been growing for the last years and has thus been increasingly supporting the concept itself (50)(51)(52)(53). An example of CRTC1-TRIM11 (50) fused melanocytoma is provided in Figure 2; like several other melanocytomas, such a putatively low-grade malignant melanocytic tumor does not likely progress from a common nevus.…”
Section: Nevi As Potential Precursors To Melanomamentioning
confidence: 90%
“…Expression of the ACTIN::MITF fusion protein is probably driven by the highly expressed promoter of the ACTB or ACTG1 N‐terminal fusion partner, analogous to the mechanism of ACTB :: FOSB fusions in pseudomyogenic haemangioendothelioma and ACTB :: GLI1 fusions in pericytoma and other mesenchymal tumours with GLI1 fusions 113–115 . This fusion protein contains the dimerisation and transcriptional activation domains of MITF , accounting for the melanocytic differentiation of these tumours 104 . The ACTG1 :: MITF fusion has also been reported in a renal cell carcinoma; this fusion protein was shown to be more stable than wild‐type MITF in in‐vitro studies 116 .…”
Section: Updates In Tumour Types Of Uncertain Nosologymentioning
confidence: 99%
“…There are emerging classes of dermal clear cell neoplasms with MITF gene fusions that, like clear cell sarcoma and cutaneous PEComa, show melanocytic differentiation and lack epidermal origin. Clear cell neoplasms with melanocytic differentiation and ACTB :: MITF and ACTG1 :: MITF fusions (collectively, ‘ ACTIN :: MITF fusions’) are the better‐characterised of this emerging group, with a recently published index series of seven tumours 104 . All seven reported clear cell neoplasms with ACTIN :: MITF fusions occurred in female patients, with six occurring in the extremities and one occurring in the breast.…”
Section: Updates In Tumour Types Of Uncertain Nosologymentioning
confidence: 99%
See 1 more Smart Citation
“…Clear cell tumor with melanocytic differentiation and MITF rearrangements: Recently, de la Fouchardiere et al [ 39 ] reported seven cases of an intradermal tumor with clear cell features and expression of melanocytic markers, harboring the ACTIN ( ACTG1 or ACTB ) ::MITF fusion. Similar to CMTCT, as well as to CSS, the neoplasm presented as a dermal nodule, occasionally involving the subcutis, in patients of all ages.…”
Section: Differential Diagnosismentioning
confidence: 99%